From the “Paris Agreement” to the “London Pact”: Political Aspects of the Democratisation of Poland’s April Constitution of 1935 - Kilian, Stanisław (Historia i Polityka, 2021)
In the history of Poland’s April Constitution of 1935, there were two attempts to democratise it, the first one in November 1939 referred to as the “Paris agreement” and the other one in September 1950 included in the formula of the “London pact”, both of which concerned the ways of implementing Article 13 defining the scope of the President’s personal powers. The “Paris agreement” introduced into political life the practice of consultation between the President and the Prime Minister; the “London pact” provided for a thorough change in the nature of the President’s relations with the Government and the planned Parliament-in-exile called the Council of National Unity, as well as strengthened the role of the political parties in political decision-making. Motivated by the notion of the modernisation of the Constitution and its adjustment to the democratic standards of Western states, the postulate to democratise it was put forward by established political actors, the Polish Socialist Party (PPS) and the National Party (SN), supported by the Independence and Democracy (NiD) party founded in exile. Appearing together as the Political Council, they took part in negotiations on the formation of a government of national unity after the death of Prime Minister T. Tomaszewski. Representatives of the Polish People’s Party did not take part in the talks; its leader, Stanisław Mikołajczyk, rejected the April Constitution “in its entirety”. The “pact” did not gain the approval of the “Castle”: the President defended the Constitution and did not accept concessions as regards Article 13. Nevertheless, the postulates of the “pact” were not nullified as they were used to build a new political construction – the National Unity – from 1954 functioning in parallel to the presidential centre. Due to the importance of the issue, the negotiations can be regarded as a breakthrough event in the political life of the émigré community. It is no exaggeration to say that the roots of the most important political events in the life of the émigré milieu go back to the “London pact”. The research goal of this article is to bring to light the political aspects of the initiative motivated by the idea of democratising the April Constitution, expressed in the formula of the “London pact”, against the background of the hypothesis that the leaders of the Political Council, behind the screen of their demand for the modernisation of the political system, aimed at weakening the position of the President as an obstacle on the way to building a new political centre – the Unity camp. They used the stage of negotiations based on the demands of the “pact” to orchestrate an anti-presidential propaganda campaign and to portray Zaleski as an opponent of the notion of unity. At the same time, they promoted the false premise that the democratisation of political life would help unblock the channels of émigré diplomacy and change the position of the Polish cause in the international arena. In this way, taking advantage of the atmosphere of distrust towards the President, they were able to launch their own political project: the National Unity, planned for as early as in 1949. For them, their participation in the Unity’s bodies opened the possibility of realising their own political ambitions reserved for politicians from President Zaleski’s closest milieu referred to as the ‘Castle entourage’.